2016
DOI: 10.1002/slct.201600355
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron based operando surface X‐ray scattering study towards structure–activity relationships of model electrocatalysts

Abstract: A novel combination of Surface X-ray Scattering techniques (SXS), i. e. GISAXS (Grazing-Incidence Small-Angle X-Ray Scattering), XRR (X-Ray Reflectivity) and SXRD (Surface X-Ray Diffraction) alongside with simultaneous detection of gaseous products by OLEMS (On-Line Electrochemical Mass Spectrometry) has been applied to study under operando conditions structure-activity relationships of a Pt model electrocatalyst.The SXS-OLEMS combination is able to follow dynamic changes in surface morphology and crystallogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In particular, On‐Line Electrochemical Mass Spectroscopy (OLEMS) was employed to follow gaseous products evolution simultaneously to the applied electrochemical treatment. Combined EC‐OLEMS measurements are commonly used in the field of electrochemistry for an accurate evaluation of electrode performance, stability, selectivity and reaction kinetics . From our studies, we emphasize the importance of using flat thin film model electrocatalyst and compositional analysis of the electrode, electrolyte as well as gaseous products to characterize the intrinsic stability and activity of earth‐abundant electrocatalysts.…”
Section: Introductionmentioning
confidence: 94%
“…In particular, On‐Line Electrochemical Mass Spectroscopy (OLEMS) was employed to follow gaseous products evolution simultaneously to the applied electrochemical treatment. Combined EC‐OLEMS measurements are commonly used in the field of electrochemistry for an accurate evaluation of electrode performance, stability, selectivity and reaction kinetics . From our studies, we emphasize the importance of using flat thin film model electrocatalyst and compositional analysis of the electrode, electrolyte as well as gaseous products to characterize the intrinsic stability and activity of earth‐abundant electrocatalysts.…”
Section: Introductionmentioning
confidence: 94%
“…Spatially resolved data are available from ex situ low-energy electron diffraction (LEED), , in situ X-ray reflectivity, and in situ electrochemical scanning tunneling microscopy (EC-STM) experiments. For a brief recent review, see the paper by Drnec et al .…”
Section: Introductionmentioning
confidence: 99%
“…Initially both {100} and {111} steps (more precisely, these step sites should be denoted as < 110 > /{100} and < 110 > /{111} respectively, that is, steps along a direction equivalent to [110] and exhibiting a square {100} or hexagonal {111} geometry) form on the roughened surface, while eventually only {111} steps remain. Advanced in situ EC-STM 16,17 and X-ray reflectivity [18][19][20][21][22] experiments are ideal tools to study this system at the atomic level. Using X-ray scattering experiments, and following the surface evolution for 20 ORCs, Ruge et al observed an increasing island size with increasing cycle number and decreasing upper potential limit 21 .…”
mentioning
confidence: 99%